Trends in the risk and burden of second primary malignancy among survivors of smoking‐related cancers in the United States. Issue 1 (24th January 2019) - Adjei Boakye, Eric; Buchanan, Paula; Hinyard, Leslie; Osazuwa‐Peters, Nosayaba; Simpson, Matthew C.; Schootman, Mario; Piccirillo, Jay F.
Abstract : While there are a growing number of cancer survivors, this population is at increased risk of developing second primary malignancies (SPMs). We described the incidence, most common tumor sites, and trends in burden of SPM among survivors of the most commonly diagnosed smoking‐related cancers. The current study was a population‐based study of patients diagnosed with a primary malignancy from the top 10 smoking‐related cancer sites between 2000 and 2014 from Surveillance, Epidemiology, and End Results data. SPM risks were quantified using standardized incidence ratios (SIRs) and excess absolute risks (EARs) per 10, 000 person‐years at risk (PYR). Trends in the burden of SPM were assessed using Joinpoint regression models. A cohort of 1, 608, 607 patients was identified, 119, 980 (7.5%) of whom developed SPM (76% of the SPMs were smoking‐related). The overall SIR of developing second primary malignancies was 1.51 (95% CI, 1.50–1.52) and the EAR was 73.3 cases per 10, 000 PYR compared to the general population. Survivors of head and neck cancer had the highest risk of developing a SPM (SIR = 2.06) and urinary bladder cancer had the highest excess burden (EAR = 151.4 per 10, 000 PYR). The excess burden of SPM for all smoking‐related cancers decreased between 2000 and 2003 (annual percentage change [APC] = −13.7%; p = 0.007) but increased slightly between 2003 and 2014 (APC = 1.6%, p = 0.032). We show that 1‐in‐12 survivors of smoking‐related cancers developed an SPM. With the significant increase in the burden of SPM from smoking‐related cancers in the last decade, clinicians should be cognizant of long‐term smoking‐related cancer risks among these patients as part of their survivorship care plans. Abstract : What's new? As more people survive cancer, understanding second primary malignancies (SPMs) is increasingly important. Here, the authors describe the incidence, most common sites, and trends in burden of second cancers in people who had survived one of the top 10 smoking‐related cancers. 1 in 12 survivors of smoking‐related cancers developed a second primary malignancy, they found. Patients with head and neck cancer had the highest risk of a second cancer, while those with urinary cancers experience the highest excess cancer burden. Oropharyngeal cancers were the most common, and lung cancers represented the largest proportion of the excess burden.